1999
DOI: 10.1001/jama.281.16.1520
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of 2 Serogroup B Outer-Membrane Protein Meningococcal Vaccines

Abstract: ENINGOCOCCAL DISEASE caused predominantly by Neisseria meningitidis serogroups A, B, and C occurs predominantly in young children and remains a substantial cause of morbidity and mortality worldwide. 1,2 In addition to causing endemic disease globally, meningococci, unlike other encapsulated bacteria, cause epidemics. Serogroup B epidemics, problematic in Norway and throughout much of Latin America in the 1980s and 1990s, 1 have recently emerged in New Zealand 3 and the United States. [4][5][6] Response to ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
237
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(253 citation statements)
references
References 38 publications
10
237
0
5
Order By: Relevance
“…This vaccine, which includes strains with serosubtypes that account for 70.6% of cases of meningococcal meningitis in Salvador, would be a candidate for use in Salvador if it proves efficacious. However, existing limitations of OMV-based meningococcal vaccines, including lower efficacy in young children (Costa et al, 1996;De Moraes et al, 1992;Sierra et al, 1991;Tappero et al, 1999), inability to induce immunological memory (Wedege et al, 1998) and failure to provide cross-protection against non-vaccine strains, may delay their use (Pollard and Levin, 2000). Alternatively, reverse vaccinology approaches have identified antigens that induce antibactericidal antibody responses against the spectrum of meningococcal serogroup B strains associated with invasive disease (Giuliani et al, 2006;Masignani et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This vaccine, which includes strains with serosubtypes that account for 70.6% of cases of meningococcal meningitis in Salvador, would be a candidate for use in Salvador if it proves efficacious. However, existing limitations of OMV-based meningococcal vaccines, including lower efficacy in young children (Costa et al, 1996;De Moraes et al, 1992;Sierra et al, 1991;Tappero et al, 1999), inability to induce immunological memory (Wedege et al, 1998) and failure to provide cross-protection against non-vaccine strains, may delay their use (Pollard and Levin, 2000). Alternatively, reverse vaccinology approaches have identified antigens that induce antibactericidal antibody responses against the spectrum of meningococcal serogroup B strains associated with invasive disease (Giuliani et al, 2006;Masignani et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Six years later, a tetravalent conjugate meningococcal vaccine, including the capsular polysaccharides of serogroups A, C, Y and W-135, was licensed for use among persons aged 11-55 years (Bilukha and Rosenstein, 2005). Despite these advances, an effective vaccine against serogroup B, a major cause of invasive meningococcal disease in many European countries and the Americas, is not currently available (Bjune et al, 1991;De Moraes et al, 1992;Sierra et al, 1991;Tappero et al, 1999;Tsolia et al, 2006). Future prevention of serogroup B disease will rely both on outer membrane vesicle (OMV) vaccines being used for specific serosubtypes and new vaccines containing multiple other antigens.…”
Section: Introductionmentioning
confidence: 99%
“…To control these outbreaks, vaccines based on the highly variable porin A protein were used, but Electronic supplementary material The online version of this article (doi:10.1208/s12248-016-9979-x) contains supplementary material, which is available to authorized users. these vaccines were not broadly effective against other invasive NmB strains (5,6).…”
Section: Introductionmentioning
confidence: 91%
“…The proportion of individuals suffering sequelae from MD in 1993 was 28.3% after one year of follow up and the lethality was 7.3%. 17,19,20 At that time, the Ministry of Health considered the outer membrane protein (OMP) meningococcal vaccine, but data suggested that this vaccine did not confer protection during a heterologous strain outbreak. 17 The aim of this study was to determine the cost-effectiveness of using 4CMenB in a one-time intervention strategy for the control of a hypothetical epidemic outbreak in Chile, a middleincome country.…”
Section: Introductionmentioning
confidence: 99%